Black Sheep and Walls of Silence - Andreas Roider
In this paper we analyze the frequently observed phenomenon that (i) some members of a team ("black sheep") exhibit behavior disliked by other (honest) team members, who (ii) nevertheless refrain from reporting such misbehavior to the authorities (they set up a "wall of silence"). Much cited examples include hospitals and police departments. In this paper, these features arise in equilibrium. An important ingredient of our model are benefits that agents receive when cooperating with each other in a team. Our results suggest that teams in which the importance of these benefits varies across team members are especially prone to the above mentioned phenomenonteams; misbehavior; wall of silence; asymmetric information